2012
DOI: 10.1159/000341435
|View full text |Cite
|
Sign up to set email alerts
|

In vivoElectrophysiological Characterization of TASK-1 Deficient Mice

Abstract: Background/Aims: TASK-1 is a potassium channel predominantly expressed in heart and brain. We have previously shown that anesthetized TASK-1-/-mice have prolonged QT intervals in surface electrocardiograms (ECGs). In addition, heart rate variability quantified by time and frequency domain parameters was significantly altered in TASK-1-/-mice with a sympathetic preponderance. Aims of the present study were the analysis of QT intervals by telemetric ECGs, to determine potential influences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…In a follow-up study, the same group showed that the key electrophysiological parameters such as electrical conduction and refractoriness were unchanged in K 2P 3.1 (Ϫ/Ϫ) mice, yet the heart rate response after premature ventricular contractions was significantly abolished. The authors suggested that the baroreceptor reflex in K 2P 3.1 (Ϫ/Ϫ) is diminished either due to sympathetic predominance or an impaired cardiac parasympathetic activity (342). In a parallel study employing A293, Decher et al…”
Section: Two-pore Domain K ϩ Channelsmentioning
confidence: 99%
“…In a follow-up study, the same group showed that the key electrophysiological parameters such as electrical conduction and refractoriness were unchanged in K 2P 3.1 (Ϫ/Ϫ) mice, yet the heart rate response after premature ventricular contractions was significantly abolished. The authors suggested that the baroreceptor reflex in K 2P 3.1 (Ϫ/Ϫ) is diminished either due to sympathetic predominance or an impaired cardiac parasympathetic activity (342). In a parallel study employing A293, Decher et al…”
Section: Two-pore Domain K ϩ Channelsmentioning
confidence: 99%
“…by guest on May 12, 2018 http://circ.ahajournals.org/ Downloaded from (P=0.030) in patients with cAF (n=10) compared with individuals with SR (n=10; Figure 1). In addition, there was a 27.6% increase of K 2P 3.1 mRNA levels in left atrial tissue (cAF, n=11 versus SR, n=4) that was not statistically significant (P=0.55; Figure 1).…”
Section: Increased K 2p 31 Levels Contribute To Atrial Remodeling Inmentioning
confidence: 99%
“…Measurements included heart rate, P wave duration, PR interval, QRS interval, rate corrected QT interval (QTc); the end of the T wave was defined as the point at which the slow component returned to the isoelectric line. For QTc calculation two different formulas were used: QT c = QT 0 /(RR 0 /100) 1/2 [26] or QTc=QT+0.154(100-RR) [27,28]. The first formula is based on the Bazett equation, and the second is a modification of the Sagie-Framingham formula.…”
Section: Surface Electrocardiography (Ecg)mentioning
confidence: 99%
“…Transvenous electrophysiological studies were performed in vivo as described previously by us and others [28,31]. Briefly, mice were anesthetized with 5% Avertin ® and a 2 F octapolar electrophysiology catheter was advanced via the jugular vein into the right atrium and right ventricle.…”
Section: Electrophysiological Study By Intracardiac Programmed Electrmentioning
confidence: 99%